The role of Action Learning in supporting cross-cultural adaptation of international students. (2nd September 2018) - Collins, Helen; Callaghan, David
ABSTRACT: We explore the reflections of a lecturer using Action Learning (AL) meetings for the dissertation module on a one-year Master's programme with a predominantly international student cohort. We focus on two concerns: to what extent does AL mitigate against the negative experiences of cross-cultural adaptation? And can we surface and share the learning that occurs when (international) scholars become practitioners and practitioners become (international) scholars? In the AL groups, many students seem more at ease with themselves, others and content in AL meetings than in other sessions. We scrutinised AL and our AL meetings to explore what makes it different and perhaps a better learning experience for the international student. This paper emerged following discussions with David, an e-learning and pedagogic specialist. Before continuing, note that there are two terms discussed in the literature: 'cross-cultural adjustment' and 'cross cultural adaptation'. 'Adjustment' refers to minor changes to cope with when facing a new situation, 'adaptation' to larger scale changes [Haslberger, Arno, and Chris Brewster. 2007. "Domains of Expatriate Adjustment with Special Emphasis on Work." Presented at the Cadiz University's VI International Workshop on Human Resource Management, Jerez, Spain]. We suggest that AL be used more often and earlier with international students.